Floating Body Effect on n-Channel Bulk FinFETs for Memory Application - Andrade, M. G. C. [UNESP]; Almeida, L. M.; Martino, J. A.; Aoulaiche, M.; Simoen, E.; Claeys, C.; Garcia, L (Ieee, 2014)
In this paper, the floating body effect (FBE) is experimentally investigated on triple gate n-channel Bulk FinFETs for 1T-FBRAM (1 transistor Floating Body Dynamic Random Access Memory) application. A difference between the Direct Current (DC) and the Alternating Current (AC) measurements corresponding with the real memory operation is shown. The large hysteresis under DC measurement related to floating body effects is observed using AC measurement only when the bulk contact is floating. Moreover, it is shown that the stored holes are not in the fins but probably in the ground plane below the junctions. Furthermore, the floating body effect in the Bulk FinFET is observed when the latter is operated like a biristor, confirming the charge storage in the junction capacitor.
Keywords: component; back bias; floating body effect; Bulk; FinFET; memory